Terezine E, bioactive prenylated tryptophan analogue from an endophyte of Centaurea stoebe. Issue 4 (16th February 2020) - Abdou, Randa; Shabana, Samah; Rateb, Mostafa E.
Abstract: Fungal endophytes are considered promising sources of new bioactive natural products. In this study, a Mucor sp. has been isolated as an endophyte from the medicinal plant Centaurea stoebe . Through bioactivity-guided fractionation, the isolation of the new bioactive terezine E in addition to the previously reported 14-hydroxyterezine D was carried out. The isolated compounds were fully characterised by HRESIMS and 1D and 2D NMR analyses. Both compounds exhibited potent antiproliferative activity against K-562 and HUVEC cell lines and antifungal efficacy against the tested fungal strains. Graphical Abstract: